Public debt consolidation and its distributional effects - Petros Varthalitis; Stelios Sakkas (The Economic and Social Research Institute (ESRI), 2019)
We build a dynamic general equilibrium model with heterogeneous households, namely Rich and Poor, and capital skill complementarity structure in the production function, to study aggregate and distributional implications of fiscal consolidation policies when the government uses a rich set of spending and tax instruments. Fiscal policy is conducted through constrained optimized fiscal rules. Our results show that, in the long run, fiscal consolidation enhances both aggregate efficiency and equity; however, it may hurt Rich households depending on which fiscal instrument takes advantage of the fiscal space created. Along the transition, wage inequality significantly increases due to the capital skill complementarity structure of the production function. Specifically, this happens because debt consolidation crowds in capital and this favours Rich (skilled) households. On the other hand, the reduction in interest rates and government bonds lead to a decrease in Rich households income coming from capital and government bonds which eventually decrease income inequality. Finally, a rather novel finding is that the combination of asset and skill heterogeneity amplifies the increase in wage inequality in the early phase of fiscal consolidation.
Keywords: E62; H52; H54; H63; 330; Debt consolidation; distributional effects; fiscal policy; optimized fiscal rules